The consumer trail: Applying best-worst scaling to classical wine attributes - Fernando Nunes; Teresa Madureira; José Vidal Oliveira; Helena Madureira (Wine Economics and Policy, 2016)
The main goal of this study is to gain a better understanding of the buying behavior of wine consumers in Portugal. More specifically, the study identifies extrinsic attributes that influence wine purchase choices in a retail store, crossing-tabulating the results with six classification variables. The authors use the best-worst scaling method with eighteen reference attributes for designing, implementing, and analyzing responses to a survey of 250 wine buyers. Results reveal that the most significant reference attribute is whether consumers had tasted the wine previously. These findings for Portugal are in accordance with what has been observed in other Western countries. The second most important attribute, region of origin, is also commonly identified in the literature as a significant attribute. The classification variables of age and gender help to explain the behavior of the majority attributes. Using a latent class analysis, the authors obtained a set of three segments that are representative of Portuguese wine consumers. The findings presented here have important implications for wineries and wine distributors in their efforts to know their consumers better in an off-premise context and thereby to maximize profit.
Keywords: 330; Best-worst scaling; Consumer choice; Off-premise setting; Wine attributes; Wine consumer